2012
DOI: 10.1007/s00404-012-2270-1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor gene polymorphisms and endometriosis risk: a meta-analysis

Abstract: Our results indicate that VEGF +936TC gene polymorphism is a risk factor for endometriosis, and not -460CT, +405CG, -2578AC, -1154GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…For rs833061 (Li et al 2013;Liang, Huang, and Fan 2012;Xu et al 2012; and rs2010963 (Fang et al 2015;Li et al 2013;Liang, Huang, and A c c e p t e d M a n u s c r i p t Fan 2012;Xu et al 2012;, our results were similar to those of earlier meta-analyses. Regarding VEGFA rs699947, our results were in line with two previous meta-analyses, (Liang, Huang, and Fan 2012;, whereas a 815 third study concluded that the risk was decreased (Li et al 2013). Only two published studies 816 were in line with the results from our meta-analysis (Lamp et al 2010;Liu et al 2009) (the 817 remaining two studies did not meet our inclusion criteria), confirming absence of an association 818 between this polymorphism and endometriosis.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…For rs833061 (Li et al 2013;Liang, Huang, and Fan 2012;Xu et al 2012; and rs2010963 (Fang et al 2015;Li et al 2013;Liang, Huang, and A c c e p t e d M a n u s c r i p t Fan 2012;Xu et al 2012;, our results were similar to those of earlier meta-analyses. Regarding VEGFA rs699947, our results were in line with two previous meta-analyses, (Liang, Huang, and Fan 2012;, whereas a 815 third study concluded that the risk was decreased (Li et al 2013). Only two published studies 816 were in line with the results from our meta-analysis (Lamp et al 2010;Liu et al 2009) (the 817 remaining two studies did not meet our inclusion criteria), confirming absence of an association 818 between this polymorphism and endometriosis.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…It is noteworthy that our result is in agreement with Zhao and colleagues [ 40 ], which suggested no evidence for an association between endometriosis and the VEGF - 2578C > A, -460 T < C, +405G > C and +936C < T SNPs, when considered together in a larger number (958 cases and 959 controls) of Australian women. Such findings appear to be corroborated by other studies which evaluated the different VEGF SNPs independently from their effect on the risk of endometriosis in different populations, and found no significant associations with - 2578C > A [ 16 , 40 ], - 460 T < C [ 16 , 34 , 40 48 ], +405G > C [ 16 , 35 , 40 , 43 , 44 , 49 , 50 ] or +936C < T [ 34 , 35 , 40 , 51 ]. Nevertheless, results from a meta-analysis suggest that the VEGF -2578C > A might be protective for the development of endometriosis [ 18 ], whereas + 936C > T was pointed as a risk factor [ 16 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…There are also studies that demonstrate the association of the VEGF +936 C/T polymorphism in Caucasian and Japanese females with endometriosis (45,46). In addition, several meta-analyses have demonstrated that the VEGF +936 C/T SNP can predispose to endometriosis (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%